Các đặc điểm thông điệp và hiệu quả truyền thông mạng xã hội của các khách sạn tại thành phố Đà Nẵng - Phan Hoàng, Long; Trà Lục, Diệp; Lê Đỗ Nguyên , Tân; Trần Thị , Hằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This paper investigates the impacts of various social media post characteristics on hotel social media marketing effectiveness. Social media marketing effectiveness is measured by the level of user engagement, namely the number of like, comment, and share of posts on a hotel’s Facebook page. Post characteristics being analyzed are post format, type of content, and posting time. The impact of the COVID-19 pandemic is also examined. Regression results using data of 1351 posts collected from the Facebook pages of twelve 5-star hotels in Da Nang city show that image or video format and contents related to discounts/promotions or hotel brand quality attract more engagement. Posting time and the COVID-19 pandemic do not significantly impact a post’s social media marketing effectiveness.